Separation Strategies for Processing of Dilute Liquid Streams. (10th November 2011) - Mandal, Sujata; Kulkarni, Bhaskar D.
Abstract : Processing of dilute liquid streams in the industries like food, agro-, biotechnology, pharmaceuticals, environment, and so forth needs special strategy for the separation and purification of the desired product and for environment friendly disposal of the waste stream. The separation strategy adopted to achieve the goal is extremely important from economic as well as from environmental point of view. In the present paper we have reviewed the various aspects of some selected universal separation strategies such as adsorption, membrane separation, electrophoresis, chromatographic separation, and electroosmosis that are exercised for processing of dilute liquid streams.